مستوى التنور التقني لدى معلمي الرياضيات بالمرحلة الابتدائية بمحافظة سراة عبيدة - آل مغني، مشعل بن ثابت بن ثابت Almughni, Meshaal Bin Thabet Bin Thabet (جمعية الثقافة من أجل التنمية, 2017)
هدفت الدراسة إلى التعرف على مستوى التنور التقني لدى معلمي الرياضيات بالمرحلة الابتدائية بمحافظة سراة عبيدة، وتعرف الفروق في مستوى التنور التقني لديهم تبعاً لمتغيرات: المؤهل العلمي ونوع التأهيل، وسنوات الخبرة، والدورات التدريبية، ولتحقيق أهداف الدراسة استخدم الباحث المنهج الوصفي المسحي، واستخدمت الاستبانة أداة للدراسة، وطبقت الدراسة على عينة مكونة من (129) معلماً، وقد أظهرت نتائج الدراسة ما يلي: 1- مستوى التنور التقني لمعلمي الرياضيات جاء بشكل عام بدرجة متوسطة بمتوسط حسابي بلغ (3.13) بالنسبة لمحاوره الثلاثة. 2- مستوى إدراك معلمي الرياضيات لأهمية التقنية جاء بدرجة كبيرة بمتوسط حسابي بلغ (3.55). 3- مستوى فهم معلمي الرياضيات للقضايا الناتجة عن التقنية واستخداماتها جاء بدرجة متوسطة بمتوسط حسابي بلغ (3.37). 4- مستوى قدرة معلمي الرياضيات على استخدام التقنية جاء بدرجة ضعيفة بمتوسط بلغ (2.47). 5- وجود فروق دالة إحصائياً بين متوسطات عينة الدراسة تجاه محور (فهم القضايا الناتجة عن التقنية واستخداماتها) تعزى لمتغير المؤهل العلمي، وجاءت الفروق لصالح افراد عينة الدراسة التي مؤهلهم العلمي بكالوريوس. 6- وجود فروق دالة إحصائياً بين متوسطات عينة الدراسة تجاه المحاور الثلاثة تعزى لمتغير نوع المؤهل، وجاءت الفروق لصالح أفراد عينة الدراسة التي نوع مؤهلهم غير تربوي. وقد أوصت الدراسة بعدد من التوصيات من أهمها: 1- عقد دورات تدريبية فعالة لمعلمي الرياضيات لإكسابهم مفاهيم ومهارات التنور التقني. 2- عمل دليل لمعلمي الرياضيات يشتمل على عناصر وقواعد توضح للمعلم أهمية التقنية وكيفية استخدامها وما القضايا الناتجة عن استخدامها في مجال الرياضيات. 3- إعادة النظر في المواد التي تختص بالتقنية واستخداماتها والتي تقدمها الكليات والجامعات من حيث تجديد وتوظيف التقنية والتأكيد على إكسابها للطلاب.
The study aimed to identify the level of Technological Literacy among the teachers of mathematics in the primary stage in Sarat Obeida Governorate. The differences in the level of Technological Literacy are defined according to the variables: the scientific qualification and the type of qualification, the years of experience and the training courses. To achieve the objectives of the study, the researcher used the descriptive method. The questionnaire was used as a tool for study. The study was applied to a sample of (129) teachers. The results of the study showed the following: 1 - The level of Technological Literacy for mathematics teachers was generally average with an average of (3.13) for the three axes. 2 - The level of awareness of mathematics teachers of the importance of technology came largely with an average of (3.55). 3 - The level of understanding of mathematics teachers of the issues resulting from technology and its uses came in a medium degree with an average of (3.37). 4 - The level of ability of mathematics teachers to use technology was weak at an average of (2.47). 5- There are statistically significant differences between the average of the sample of the study towards the axis (understanding of the issues resulting from the technology and its uses) due to the variable of scientific qualification. 6 - There were statistically significant differences between the average of the sample of the study towards the three axes due to the variable type of qualification, and the differences were for the benefit of the sample members of the study whose type of education is non - educational. The study recommended a number of recommendations, the most important of which are: 1 - Holding effective training courses for mathematics teachers to impart the concepts and skills of Technological Literacy. 2- Preparing a guide for mathematics teachers that includes elements and rules that explain to the teacher the importance of technology and how to use it and the issues resulting from its use in mathematics. 3. Reconsidering the materials related to the technology and its uses provided by the colleges and universities in terms of renewing and employing the technology and emphasizing its acquisition of students.
Keywords: التعليم الابتدائي -- تكنولوجيا المعلومات -- التنور التكنولوجي -- معلمو الرياضيات -- السعودية